1987
DOI: 10.1111/j.1471-0528.1987.tb02355.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to rubella among women of child‐bearing age

Abstract: The results of testing for rubella antibodies in over 6000 sera from women of child-bearing age are reported and analysed according to pregnant state, age, country of origin and social class. There was no difference between the rubella seroprevalence rates in women who were pregnant and in those who were contemplating pregnancy in the future. Likewise, women (either pregnant or non-pregnant) who were young enough to have been offered rubella vaccine at school were not more likely to be immune to rubella than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Seroprevalence is higher in European women (93.2%) than in women of African (86.7%) and Asian origin (78.4%) (Lever et al, 1987). In our study among pregnant women in Turkey, the seroprevalence was similar to that of European women.…”
Section: Discussionsupporting
confidence: 57%
“…Seroprevalence is higher in European women (93.2%) than in women of African (86.7%) and Asian origin (78.4%) (Lever et al, 1987). In our study among pregnant women in Turkey, the seroprevalence was similar to that of European women.…”
Section: Discussionsupporting
confidence: 57%
“…This study in Sydney found relatively high levels of immunity to rubella amongst confinements and has identified groups which might possibly be targeted for population‐based educational interventions aimed at improving immunity amongst women of child‐bearing age. As in other countries, country of birth was found to be a highly significant factor in determining rubella immune status 7–10 . Specifically, we identified that Asian‐born women were 7 times more likely to be non‐immune to rubella than Australian‐born women.…”
Section: Discussionmentioning
confidence: 53%
“…A study has reported 5-50% incidence rate of congenital Rubella when the mother is infected in the first trimester of her pregnancy (Miller et al, 1982). In a study, approximately 12% of pregnant women were found to be seroposititve for rubella and about 10-20% of women in the child bearing age were susceptible for the rubella infection (Rubella and Pregnancy, 1993;Lever et al, 1987). Our study has reported a statistically significant difference between the two groups i.e., cases and controls.…”
Section: Resultsmentioning
confidence: 99%